A discussion on the user intention of golfers toward golf GPS navigation. (16th March 2015) - Huang, Jen-Min; Ho, Tu-Kuang; Liu, Yen-Chun; Lin, Yu-Hsiang
Abstract : Purpose: – This paper aims to examine the user's willingness of golfers toward the use of GPS navigation based on the technology readiness and acceptance models. Design/methodology/approach: – This study developed the research structure based on the theory of the technology acceptance and readiness model to address the relationship between technology readiness, perceived usefulness, perceived ease of use, user's attitude and behavioral intention. A purposive sampling questionnaire was used in this study to investigate golf participants in Central Taiwan. In all, 245 copies of the questionnaire were issued. About 240 copies were returned and after removing the invalid copies, there were 230 valid questionnaires for a valid response rate of 95.8 per cent. Findings: – The research results indicated that technology readiness has a significant influence on perceived usefulness, technology readiness has a significant influence on perceived ease of use, perceived ease of use has a significant influence on perceived usefulness, perceived usefulness has no significant influence on user's attitude, perceived ease of use has a significant influence on user's attitude, user's attitude has no significant influence on behavioral intention and perceived usefulness has a significant influence on behavioral intention. Originality/value: – The technology acceptance model has been widely used to examine user's acceptance and willingness toward computer technology or an information product. This study, hence, is based on this model to investigate the user's willingness of golfers toward golf GPS and shall serve as a reference for future golf sports promotion and device R&D.